Two-scale damage failure analysis of 3D braided composites considering pore defects. (15th March 2021) - Ge, Lei; Li, Huimin; Zheng, Huayong; Zhang, Chun; Fang, Daining
Highlights: Strength formulas considering pore defects are employed and verified. Different void generating methods across two scales are established. Two-scale damage method coupled with representative volume cell is developed. Results by the meso-model considering pore defects agree well with experiments. The strength and damage mechanism are greatly determined by pore defects. Abstract: Pore defects tend to form in the manufacturing process, and significantly influence the mechanical properties of 3D braided composites. To predict the failure modes and strength properties considering pore defects, a two-scale progressive damage method coupled with representative volume cell (RVC) has been developed due to the periodic feature across different scales of 3D braided composites. Different void generating methods across two scales are established, including the element-model by elements chosen and the void-model by voids explicitly constructed. The user-defined material subroutine (UMAT) is coupled in the nonlinear finite element analysis software ABAQUS to implement the damage model for micro and meso numerical models. Also, the Chamis model considering pore defects are employed and verified. It shows that results by void-model agree well with the Chamis model and the experimental data. And, the void-model is superior to the element-model when predicting the mechanical properties of braided composites. The pore defects weaken the matrix properties, and therefore largely determine the strength and damage mechanism of 3D braided composites with large braiding angle. This two-scale damage failure analysis method by void-model is effective to predict strength and damage failure mechanism of 3D braided composites considering pore defects.